"Doing Race": Latino Youth's Identities and the Politics of Racial Exclusion. (December 2014) - Flores-González, Nilda; Aranda, Elizabeth; Vaquera, Elizabeth
For most Latino youth, Latinos constitute a separate, while diverse, racial group. Our study demonstrates that, when asked about their identities, Latino youth do not follow conventional U.S. racial categories. Although they prefer to identify by national origin or panethnicity, they consider themselves to be part of a racial group rather than an ethnic group, as the U.S. Census designates them. Using findings from in-depth semistructured interviews with two samples of young adults in Chicago and Central Florida, this research joins the long-standing debate on the conceptual division between race and ethnicity arguing that there is a mismatch between existing sociological understandings of race and ethnicity and the current racial ideas and racial practices among Latino youth. There is also a mismatch between institutional measures of "race, " such as those found in the U.S. Census, and Latinos' self-understandings of where they belong in the U.S. racial hierarchy. We suggest that not being officially designated as a racial group leads to the erosion of perceptions of belonging among Latinos to a nation in which being a member of a racial group allows for visibility and claims-making in a multiracial society.